Indonesian Marine Geology Research Vessels: Their Capacity and Activity - Ai Yuningsih; Wahyu Pandoe; Herman Darman (Berita Sedimentologi, 2015)
About two thirds of Indonesian territory is covered by sea, below which there is little-documented and fascinating geological features which require study. Observing and understanding this geology is obviously technically more difficult than for the onshore. Thus, knowledge of the submarine geology relies on research and commercial ships.The marine geology of Indonesia has been studied since the 18th century. Two French ships called Boudeuse and Etoile, and led by De Bougainville sailed to collect data in 1768. Since then many other research vessels came and were run by researchers from the UK, Austria, the Netherlands, USA, Germany and Japan. In late 1980s Indonesia bought its own research vessel, Baruna Jaya 1, and since then has built its own fleet of research vessels.